Analisis Implementasi Program Poned Dalam Penurunan Angka Kematian Ibu di UPTD Puskesmas Patani: Analysis of Poned Program Implementation in the Decrease in Maternal Mortality in UPTD Puskesmas Patani - Suriyanti Akbar; Eka Vicky Yulivantina; Yustina Ananti (Journal of Health, 2025)
The maternal mortality rate in North Maluku was 255 per 100,000 live births in 2022, higher than the SDG target of 70. Main causes included hemorrhage (21. 14%), hypertension (26. 34%), and infections (2. 76%). Most deaths happened postpartum (60. 90%). This study used a phenomenological approach with informants from the Head of the Health Office, Head of TU, Doctors, Nurses, Midwives, and postpartum womenThe study aimed to evaluate how well policies work, examine challenges in human resources and communication, and understand the traits and views of program implementers. Results should enhance program execution to lower Maternal Mortality Rate (MMR) at UPTD Puskesmas Patani using Van Meter Van Horn theory. The research used in-depth interview guidelines about PONED implementation. It found that: 1. Standards and policy objectives are implemented. 2. Human resources are below standard. 3. Communication between organizations is poor. 4. Implementing agent characteristics are good. 5. Implementer attitudes are good. 6. The environment is good. Implementation of the PONED program at the UPTD Puskesmas Patani according to Van Meter Van Horn's theory to reduce maternal mortality rates (MMR) has gone well in 4 elements: standards, measures, targets, and policy objectives; characteristics of implementing agents; attitudes of implementers; and the social, economic, and political environment. However, 2 elements, namely human resources and communication between organizational characteristics, have not gone well. This study should focus on the implementation of the PONED program and more in-depth exploration of the patient referral process in emergencies.